Teaching Factory (TeFa) Learning Strategy and Risk Management at SMK Negeri 1 Garut - Pratiwi, Ratih; Cahyana, Agus; Sastrawan, Uding; Pratama, Aldi Adi (AIBPM Publisher, 2022)
Absorption of SMK graduates in the world of work is said to still beproblem crucia lTeFa learning at SMK Negeri 1 Garut by producing products/services resulting from student learning and the use of products/services by the community. Competence in Accounting and Financial Institutions (AKL) of SMK Negeri I Garut is still transforming towards the implementation of TeFa learning. The research methodology used includes a population consisting of students involved in TeFa, TeFa administrators, and educators. Data were obtained through questionnaires, observations and focus group discussions; and this research is a descriptive study using the SWOT analysis method and risk management review on the TeFa component. The results of the study indicate that the development TeFa learning uses a strength-opportunity of approach with moderate risk analysis results. The implication of implementing the (Strength-Opportunity) strategy is to accelerate the implementation of TeFa learning and have the impact of producing according to market